2022
DOI: 10.29196/jubpas.v30i1.4134
|View full text |Cite
|
Sign up to set email alerts
|

Key Generation for Vigenere Ciphering Based on Genetic Algorithm

Abstract: Cryptography is a science securing of information. Encryption requires impregnable keys to encrypt or decrypt data these keys should be unpredictable and not easily to break. In this research we use genetic algorithm to generate keys for vigenere cipher. The best key is used to perform encryption. The keys created by genetic algorithm are tested for randomness by using the entropy test. The entropy calculation shows that randomness of key generated based on genetic processing is better than chosen key in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Garg et al [ 28 ] suggested a genetic algorithm and DNA cryptography-based encryption scheme for Fog Networks. Hussein and Ayoob [ 29 ] came up with a secure key generation scheme to enhance Vigenere Cipher using the concepts of GA.…”
Section: Related Workmentioning
confidence: 99%
“…Garg et al [ 28 ] suggested a genetic algorithm and DNA cryptography-based encryption scheme for Fog Networks. Hussein and Ayoob [ 29 ] came up with a secure key generation scheme to enhance Vigenere Cipher using the concepts of GA.…”
Section: Related Workmentioning
confidence: 99%
“…By considering the local relationships between agents, ABMs can simulate how simple the interactions between agents can give rise to complex patterns of behavior at the system level. These powerful characteristics have motivated the use of ABM in several applications, such as characterization of the immune system [28], social behavior [29], [30], image processing [31], image colorization [32], fire spreading [33], and spread in epidemics [34], among others [35], [36], [37].…”
Section: Introductionmentioning
confidence: 99%